(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
This article describes the content of test programs, which is of practical importance in the training process for predicting competitive results in competitive swimming. The experiment involved 24 athletes of the III-d grade and above level II. The study was conducted in the youth athletic center № 3 in Lutsk and in the sports club of Lutsk National Technical University in the 2022–2023 academic year. Based on the analysis of practical experience, we have developed test programs for swimming in full coordination on the arms and legs for swimmers from the third to the first athletic title, freestyle and specializing in short/medium/long courses. There are sample calculations of controlled testing in full coordination for athletes specializing in 1500 meters freestyle. Testing: 15 x 100 meters freestyle and an average speed is 90–95%. The rest period between the distances is 1 min. 30 seconds. The calculations were carried out in the following way: every hundred meter race and the time was recorded in the same sequence as the athlete was swimming. The figures obtained in seconds were summed up and the total amount was initially 1135,09 seconds. 60,25 seconds were added. This is the time of correction for the result for 1500 meters freestyle. So, the total time in seconds 1195,34 was transferred into minutes and seconds and obtained 19,55,34. Thus, the time 19,55,34 corresponds to the level of physical fitness of an athlete at this distance at the time of testing. The developed test programs made it possible to determine the physical fitness of athletes, their readiness for competition. This gave us the opportunity to predict the competitive result, to alternate work and rest during the lesson, to make changes in the content of the annual training cycle or its periods.